Coulombic effects on magnetoconductivity oscillations induced by microwave excitation in multisubband two-dimensional electron systems - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We develop a theory of magneto–oscillations in photoconductivity of multisubband two-dimensional electronsystems which takes into account strong Coulomb interaction between electrons. In the presence of a magnetic field oriented perpendicular, internal electric fields of fluctuational origin cause fast drift velocities of electronorbit centers which affect probabilities of inter-subband scattering and the photoconductivity. For the electron system formed on the liquid helium surface, internal forces are shown to suppress the amplitude of magnetooscillations, and change positions of magnetoconductivity minima which evolve in zero-resistance states for high radiation power.